Înmormântări din situl arheologic de la Cetățeni - Măndescu, D.; Constantinescu, M. (Materiale și Cercetări Arheologice)
The core of the paper is represented by three archaeological features researched more than six decades ago by Dinu V. Rosetti (1899−1982), in the site at Cetățeni : two funerary / cult features from the Late Iron Age (known as “the royal tomb among rocks”, sometimes referred to as the “sanctuary among rocks”, respectively „tomb no. 1 under Colțul Doamnei”) and a medieval grave considered decisive for the dating of church no. 3 there to the mid 13 th century at the latest. These features were never published in detail by the author of the excavations, and thus they were regarded with caution. Based on the osteological remains identified at the Institute of Anthropology “Francisc I. Rainer” in Bucharest, and some elements preserved from the archaeological grave goods, scattered among the collections of four museums (Argeș County Museum, National History Museum of Romania, Câmpulung Municipal Museum and “King Ferdinand I” National Military Museum), the article resumes the debate on these features from a new, interdisciplinary perspective, including the anthropological study and radiocarbon dating. Following a similar approach, two other funerary discoveries made at Cetățeni are taken into consideration : a grave probably also excavated by D. V. Rosetti in the medieval cemetery nearby the churches and a more recent reburial from the peak of Cetățuia hillock